Influence of technical and geographical parameters on the range of language information retrieval in solving applied problems - Azarenko , Olena; Honcharenko , Yulia; Divizinyuk , Mykhailo; Mirnenko , Volodymyr; Strilets , Valeriy (Social Development and Security, 2021)
This article is devoted to the consideration of the main technical parameters of acoustic means and geographical factors of the area on the range of language information in the solution of applied problems of protection of critical infrastructure from terrorist acts. First, the characteristics of the main technical parameters of acoustic means of recording speech information are given. It is shown that the main technical parameters of acoustic means of recording speech information are the sensitivity of the microphone, its direction, the operating frequency band and the recognition factor. Then consider the concept of energy range detection of acoustic signals. It is shown that the energy range of the acoustic means is the largest calculated value of the distance, which ensures the equality of the energy potential of the acoustic and the regularity of the decrease in the intensity of the propagating acoustic wave. Then the geometric range of detection of acoustic signals was analyzed, taking into account the terrain around the critical infrastructure object. It is shown that the geometric range of acoustic signals will be determined by the geometric distance of the visible horizon, taking into account the positive and negative terrain, the presence of housing, forests and water, and the state of the underlying surface around the critical infrastructure in the direction determined by the acoustic device. Then the expected range of speech information is considered as a result of the ratio of energy and geometric activities for the detection of acoustic signals. It is shown that the expected range of speech information is defined as the product of the energy range of detection of acoustic signals on the value of the coefficient of influence of the environment in the surface layers of the atmosphere. If the obtained result exceeds the value of the geometric detection range of the acoustic signal, the value of the expected range is the geometric detection range.